State-of-the-Art Liquid Crystals Research in Japan - Yamada, Shigeyuki; Isoda, Kyosuke; Ichikawa, Takahiro; Kaneko, Kosuke; Kondo, Mizuho; Sakurai, Tsuneaki; Seki, Atsushi; Hara, Mitsuo; Watanabe, Go (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue includes ten papers by 45 authors, including excellent cutting-edge research from Japan. Looking at the papers reported here, Japan's liquid crystalline research is a global pioneer within this field. It is clear that Japanese liquid crystalline research will further develop in the future.